Methylicorpusculum oleiharenae gen. nov., sp. nov., an aerobic methanotroph isolated from an oil sands tailings pond. Issue 4 (19th April 2020) - Saidi-Mehrabad, Alireza; Kits, Dimitri K.; Kim, Joong-Jae; Tamas, Ivica; Schumann, Peter; Khadka, Roshan; Strilets, Tania; Smirnova, Angela V.; Rijpstra, W. Irene C.; Sinninghe Damsté, Jaap S.; Dunfield, Peter F.
Abstract : An aerobic methane oxidizing bacterium, designated XLMV4 T, was isolated from the oxic surface layer of an oil sands tailings pond in Alberta, Canada. Strain XLMV4 T is capable of growth on methane and methanol as energy sources. NH4 Cl and sodium nitrate are nitrogen sources. Cells are Gram-negative, beige to yellow-pigmented, motile (via a single polar flagellum), short rods 2.0–3.3 µm in length and 1.0–1.6 µm in width. A thick capsule is produced. Surface glycoprotein or cup shape proteins typical of the genera Methylococcus, Methylothermus and Methylomicrobium were not observed. Major isoprenoid quinones are Q-8 and Q-7 at an approximate molar ratio of 71 : 22. Major polar lipids are phosphoglycerol and ornithine lipids. Major fatty acids are C16 : 1 ω8+C16 : 1 ω7 (34 %), C16 : 1 ω5 (16 %), and C18 : 1 ω7 (11 %). Optimum growth is observed at pH 8.0 and 25 °C. The DNA G+C content based on a draft genome sequence is 46.7 mol%. Phylogenetic analysis of 16S rRNA genes and a larger set of conserved genes place strain XLMV4 T within the class Gammaproteobacteria and family Methylococcaceae, most closely related to members of the genera Methylomicrobium and Methylobacter (95.0–97.1 % 16S rRNA gene sequence identity). In silico genomic predictions of DNA–DNA hybridization values of strain XLMV4 T to the nearest phylogenetic neighbours were all below 26 %. On the basis of the data presented, strain XLMV4 T is considered to represent a new genus and species for which the name Methylicorpusculum oleiharenae is proposed. Strain XLMV4 T (=DSMZ DSM 27269=ATCC TSD-186) is the type strain.